Phytochemical Composition and Antioxidant Potential of Hyphaene thebaica Fruit - Muhammad Mubarak Dahiru; Margret Samuel Nadro (Borneo Journal of Pharmacy, 2022)
The nature and application of medicinal plants in managing complications of various ailments are attributed partly to the presence of different phytochemicals. Oxidative stress due to increased levels of reactive oxygen species is a challenge in the management of such ailments, which might lead to death. This study aimed to determine the phytochemical composition and antioxidant potential of Hyphaene thebaica fruit. The phytochemicals in methanol, aqueous, and ethyl acetate extract were qualitatively determined, followed by quantitation of the ethyl acetate extract as it contains phytochemicals absent in the other extracts. The in vitro antioxidant potential of the ethyl acetate extract of H. thebaica fruit was also determined. The result revealed the presence of alkaloids, saponins, terpenoids, and flavonoids in all the extracts. However, steroids were not detected in the aqueous extract, and glycoside was detected only in the ethyl acetate extract. Flavonoids (5.80±0.20%) were higher than all the other phytochemicals in the ethyl acetate extract, followed by saponins which were present up to 2.50±0.11%, then terpenoids. Glycosides were present in higher amounts compared to steroids. However, alkaloids (0.08±0.05%) were in smaller amounts compared to the other phytochemicals quantified. The antioxidant activity showed a concentration-dependent increase in absorbance of the extract as displayed by the standard (ascorbic acid). The extract had an IC50 of 52.21 µg/mL, significantly (p <0.05) higher than that of the standard (14.10 µg/mL). Due to its phytochemical composition and antioxidant activity, H. thebaica can be used as a medicinal plant.